2012
DOI: 10.3846/20290187.2011.633247
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Narrative Fetishism as the Source for Creativity in the Urban Space / Trauma Ir Naratyvinis Fetišizmas Kaip Kūrybingumo Šaltinis Miesto Erdvėje

Abstract: The paper analyzes trauma as the source for creativity in the urban space. There are two strategies to find a way to live with traumatic experience. The first way, according to Sigmund Freud, is "the work of mourning", which by constant remembering and repeating trauma in the language of tropes and figures allows to integrate discontinuous traumatic experience thus partly expunging trauma. Another strategy for dealing with trauma was described by Eric L. Santner's term "narrative fetishism". This strategy supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This proven and varying presence of codependency, neuroticism, binge drinking, and alcoholic terminology among characters suggests Patricia Highsmith's use of projection as a coping mechanism for AUD. Studies by Yankov (2012) and Harvard Health Publishing (2021) support this general finding; the former reveals the tendency for traumatic experiences to influence written work and the latter confirms writing as a common coping mechanism for its projective value. As this further relates to Patricia Highsmith individually, her attempt at coping with AUD began by projecting codependency and neuroticism onto the vast majority of written situations both between characters and within a single character.…”
Section: Authorial Applicationmentioning
confidence: 87%
See 1 more Smart Citation
“…This proven and varying presence of codependency, neuroticism, binge drinking, and alcoholic terminology among characters suggests Patricia Highsmith's use of projection as a coping mechanism for AUD. Studies by Yankov (2012) and Harvard Health Publishing (2021) support this general finding; the former reveals the tendency for traumatic experiences to influence written work and the latter confirms writing as a common coping mechanism for its projective value. As this further relates to Patricia Highsmith individually, her attempt at coping with AUD began by projecting codependency and neuroticism onto the vast majority of written situations both between characters and within a single character.…”
Section: Authorial Applicationmentioning
confidence: 87%
“…This is because lived experiences of any significance or connotation can affect creative work, either intentionally or unintentionally (Hatavara et al, 2017). However, Yankov (2012) observes that traumatic experiences often have the most potent impact on creative work, specifically writings; discussed in the article is the term "narrative fetishism," which refers to the idea that one may have an inability to express trauma through oral communication, leading to the integration of trauma and writings. Numerous studies have similarly found writing to be a coping mechanism for those experiencing anxiety and depression in an attempt to overcome emotional inhibition or suppression (Harvard Health Publishing, 2021;Kasi et al, 2012).…”
Section: Impact Of Lived Experiences On Creative Workmentioning
confidence: 99%
“…Attention to the city and architecture is associated with a growing interest in the topic of memory, national and local identity and the corresponding forms of narrative (Assman, 2015;Kačerauskas, 2008;Piskunova, Starostova, & Yankov, 2015;Yankov, 2011). In our case, architecture appears as a structure of crystallization of a socially formed experience.…”
Section: Languages Of Describing Architecture As a Part Of The Urban mentioning
confidence: 99%